Evaluate the Efficacy of Intracameral and Sub-Conjunctival Dexamethasone in Preventing Postoperative Inflammation in Patients Undergoing Cataract Surgery - Syed Shujaat Ali Shah, Safeet Shahbaz Khan, Muhammad Naeem, Aleem Muhammad Mansha Chauhdary, Lt Col Ayyaz Hussain Awan, Muhammad Zia Iqbal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to assess the efficacy of injecting dexamethasone intracamerally and subconjunctivally into individuals having cataract surgery in order to lower the risk of inflammation following the procedure. Methods: This study included 160 patients, who underwent cataract surgery and were no older than 14 years. Group I consisted of 80 patients who got subconjunctival dexamethasone, whereas group II, also consisting of 80 patients, received intracameral injections of dexamethasone. On the first and third post-operative days, slit lamps were used to examine post-operative inflammation. SPSS 24.0 was used to analyze all data. Results: A significant difference was identified between the two groups, with a p-value of less than 0.005. In group I, postoperative inflammation was found in 25 patients, which accounts for 31.3% of the total, while in group II, it was found in 5 patients, which accounts for 3.8% of the total. Conclusion: It was determined that intracameral injection of dexamethasone is far more successful than sub-conjunctival injection for preventing inflammation after cataract surgery in youngsters. Keywords: Intracameral, Post-operative Inflammation, Cataract surgery, Sub-conjunctival, Dexamethasone